EFEKTIVITAS TEKNIK SELF MANAGEMENT UNTUK MENGATASI PERILAKU PROKRASTINASI AKADEMIK - Fadhillah, Nurul; Asrori, Muhamad; Fergina, Ana (Universitas Tanjungpura, 2023)
This study aims to examine the effectiveness of self-management techniques in eliminating academic procrastination in class VIII students of SMP Negeri 18 Pontianak. The research method used is quantitative in the form of a Pre-Experimental Design research with a Pre-test